Knee pain in the community: risk factors, incidence, and outcome - Ingham, Sarah Louise (2010)
Background: Knee pain affects 1 in 4 people over 55 years, and is a leading cause of disability in the elderly (Peat et al, 2001). Whilst the prevalence of knee pain has been examined, the natural history of knee pain and associated risk factors remain unknown (O’Reilly, 1996).